EVALUATING THE SUCCESS OF CLOUD ACCOUNTING IN CAFES AND RESTAURANTS IN PEMATANG SIANTAR: PERSPECTIVE OF THE INFORMATION SYSTEM SUCCESS THEORY - Fitri Ramadhani; Sambas Ade Kesuma; Parapat Gultom (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The implementation of cloud accounting in cafes and restaurants is expected to improve operational efficiency, enhance the accuracy of financial reports, and provide net benefits for businesses. However, in practice, the success of implementation still faces several challenges, such as suboptimal system quality, information quality, and service quality.This study aims to analyze the effect of system quality, information quality, and service quality on cloud accounting success, as well as the effect of cloud accounting success on net benefits among cafes and restaurants in Pematang Siantar City. The research design employs a quantitative approach using primary data. The sample consists of owners or managers, and accounting and finance staff from 170 cafes and restaurants in Pematang Siantar City. Sampling was conducted using a full sampling technique, resulting in a total of 265 respondents. Data analysis was conducted using Structural Equation Modeling (SEM). The findings indicate that system quality, information quality, and service quality have a positive effect on cloud accounting success, and cloud accounting success positively affects net benefits. Furthermore, cloud accounting success is proven to mediate the relationship between system quality, information quality, and service quality with net benefits.